1982
DOI: 10.1182/blood.v59.2.428.428
|View full text |Cite
|
Sign up to set email alerts
|

Severe-glucose-6-phosphate dehydrogenase (G6PD) deficiency associated with chronic hemolytic anemia, granulocyte dysfunction, and increased susceptibility to infections: description of a new molecular variant (G6PD Barcelona)

Abstract: Molecular, kinetic, and functional studies were carried out on erythrocytes and leukocytes in a Spanish male with G6PD deficiency, congenital nonspherocytic hemolytic anemia (CNSHA), and increased susceptibility to infections. G6PD activity was absent in patient's red cells and was about 2% of normal in leukocytes. Molecular studies using standard methods (WHO, 1967) showed G6PD in the patient to have a slightly fast electrophoretic mobility at pH 8.0 with otherwise normal properties (heat stability at 46 degr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

1985
1985
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Most researchers explained the potential mechanism by which LG6PD could result in the disorder of oxidative stress and hence, in the malfunctioning of granulocytes [30][31][32][33] . Some researchers 5,30 suggested that LG6PD could reduce NADPH levels, thus decrease the production of nitric oxide, superoxide and hydrogen peroxide in leucocytes, and weaken the immune function thereof, thereby increase the susceptibility to pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…www.nature.com/scientificreports www.nature.com/scientificreports/ Most researchers explained the potential mechanism by which LG6PD could result in the disorder of oxidative stress and hence, in the malfunctioning of granulocytes [30][31][32][33] . Some researchers 5,30 suggested that LG6PD could reduce NADPH levels, thus decrease the production of nitric oxide, superoxide and hydrogen peroxide in leucocytes, and weaken the immune function thereof, thereby increase the susceptibility to pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…and serological test results. Age was split into three groups (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39), and 40-49 years old), while nationality was categorized as 'Han' and 'others' . Educational level was categorized into two groups (bachelor degree or above, high school or below).…”
Section: Definition Of Variables Variables In This Study Included Dementioning
confidence: 99%
“…For example, the generation of NO by nitric oxide synthase (NOS) and other ROS by NADPH oxidase in human cells is NADPH-dependent. 23,24) We previously found that in G6PD-deficient granulocytes the production of NO, superoxide and H 2 O 2 is impaired due to the decrease of NADPH. 25) In this regard, patients with low G6PD activity may have increased radiation resistance due to impaired production of free radicals which are responsible for the killing of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…G6PD Mediterranean is one of the most common G6PD-deficient variants in many parts of the world [2]. Two subtypes of G6PD Mediterranean have been identified previously: the G6PD Mediterranean-Middle East subtype (c.563 C>T, 1311 C>T, IVS11 nt 93 T>C) and the G6PD Mediterranean India-Pakistan subtype (c.563 C>T, 1311 C, IVS11 nt 93 T).…”
mentioning
confidence: 99%
“…Two subtypes of G6PD Mediterranean have been identified previously: the G6PD Mediterranean-Middle East subtype (c.563 C>T, 1311 C>T, IVS11 nt 93 T>C) and the G6PD Mediterranean India-Pakistan subtype (c.563 C>T, 1311 C, IVS11 nt 93 T). The former has been found in Mediterranean countries and Middle Eastern countries; the latter has been found in India and Pakistan mainly [2][3][4], but these have not been reported in China before. In the present study, we have identified a case of G6PD deficiency with G6PD Mediterranean-Middle East subtype in China for the first time.…”
mentioning
confidence: 99%